(untitled) (European Journal of Pure and Applied Mathematics, 2020)
The pseudo-Lindley distribution which was introduced in Zeghdoudi and Nedjar (2016) is studied with regards to it upper tail. In thatÂ regard, andÂ when the underlying distribution function follows the Pseudo-Lindley law, we investigateÂ the the behavior of its values, the asymptotic normality of the Hill estimator and the double-indexed generalized Hill statistic process (Ngom and Lo, 2016), the asymptotic normality of the records values and the the moment problem.